건강 검진자에서의 Helicobacter pylori 혈청학적 유병률 - 임정윤; Jeong Yoon Yim; 최승호; Seung Ho Choi; 박민정; Min Jeong Park; 김영선; Young Sun Kim; 임선희; Sun Hie Lim; 조경란; Keong Ran Choi; et al. (The Korean journal of medicine, 2006)
목적: 최근 H. pylori 제균 치료가 비교적 흔히 이루어지고 있고, 사회경제적 요소가 향상되고 있어 H. pylori 양성률에 감소가 있을 것으로 예상 된다. 이에 성인 건강 검진자를 대상으로 H. pylori 혈청학적 양성률 및 이에 관련된 인자에 대해 분석해보고자 하였다. 방법: 2004년 11월부터 2005년 6월까지 8개월간 서울대학교병원 강남센터에 건강 검진을 목적으로 내원한 20세 이상의 성인 남녀를 대상으로 하여 H. pylori에 대한 혈청학적 검사와 설문조사를 시행하였다. 결과: 전체 대상자 7,676명의 H. pylori에 대한 혈청학적 양성률은 56.7%으로 남자에서는 57.0%, 여자는 43.0%였으며 연령별로는 50대가 가장 높았는데 14.8%에서 H. pylori 제균 치료 경험을 가지고 있었다. H. pylori 제균 치료 병력이 없는 군에서의 H. pylori 혈청학적 양성률은 59.7%이었고, 소화기 증상이 없는 대상에서는 61.3%였다. H. pylori 감염의 위험요인에 대한 다변수 분석시 H. pylori 혈청학적 양성률과 소화기 증상유무, 교육 정도와는 연관성이 없었으나 남자와 높은 연령, 지방과 저소득층이 양성률에 위험요소로 작용하는 것으로 나타났다. 결론: 한국인에서의 H. pylori 양성률은 7여년 전보다 낮아진 것으로 나타났는데 이는 제균 치료와 함께 사회경제적 향상도 영향을 준 것으로 생각된다. Background: H. pylori-associated gastrointestinal diseases have been widely recognized. The aim of this study was to investigate the seropositivity of H. pylori in health check-up subjects and to find out the relating factors. Methods: From November 2004 through June 2005, total 7,676 health check-up subjects (age≥20) responded to the self administered questionnaires. The prevalence of H. pylori was assessed by measuring anti-H. pylori IgG antibodies. Results: The overall seropositivity was 56.7% in 7,676 and 1,137 (14.8%) has been found to have history of H. pylori eradication therapy. The seropositivity rate of H. pylori was 61.3% (2,653) in 4,328 subjects without history of H. pylori eradication and current gastrointestinal symptoms. Seroprevalence of H. pylori was significantly lower in 20~29 years old, female, high income and subjects from Seoul respectively. Conclusions: The seropositivity of H. pylori in 2004~2005 is found to be 61.3% in subjects without history of H. pylori eradication and current gastrointestinal symptoms. This seems to be lower than 66.9%, the seroprevalence rate in asymptomatic Korean population in the age of ≥16 years in 1998. This decrease might be caused by improvement of socioeconomic status.(Korean J Med 70:636-642, 2006)